Correction: Chemical fixation of CO2 into cyclic carbonates by azo-containing Schiff base metal complexes. (19th August 2015) - İkiz, Mesut; İspir, Esin; Aytar, Emine; Ulusoy, Mahmut; Karabuğa, Şemistan; Aslantaş, Mehmet; Çelik, Ömer
Abstract : Correction for 'Chemical fixation of CO2 into cyclic carbonates by azo-containing Schiff base metal complexes' by Mesut İkiz et al., New J. Chem., 2015, DOI: ; Web:10.1039/c5nj00571j .